2011
DOI: 10.1021/jp1118184
|View full text |Cite
|
Sign up to set email alerts
|

13C NMR Studies of Hydrocarbon Guests in Synthetic Structure H Gas Hydrates: Experiment and Computation

Abstract: 13C NMR chemical shifts were measured for pure (neat) liquids and synthetic binary hydrate samples (with methane help gas) for 2-methylbutane, 2,2-dimethylbutane, 2,3-dimethylbutane, 2-methylpentane, 3-methylpentane, methylcyclopentane, and methylcyclohexane and ternary structure H (sH) clathrate hydrates of n-pentane and n-hexane with methane and 2,2-dimethylbutane, all of which form sH hydrates. The 13C chemical shifts of the guest atoms in the hydrate are different from those in the free form, with some car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 33 publications
(72 reference statements)
3
30
0
Order By: Relevance
“…The spectrum between 20 and 40 ppm shows the chemical shifts of MCH in the large cage, there is some overlap with those of the liquid phase. 37 The 13 C NMR chemical shifts of CH 3 F in the different clathrate hydrate structures are reported in Table I.…”
Section: A Nmr Studiesmentioning
confidence: 99%
“…The spectrum between 20 and 40 ppm shows the chemical shifts of MCH in the large cage, there is some overlap with those of the liquid phase. 37 The 13 C NMR chemical shifts of CH 3 F in the different clathrate hydrate structures are reported in Table I.…”
Section: A Nmr Studiesmentioning
confidence: 99%
“…Clathrate hydrates are crystalline solids in which a water lattice (the "host") creates cages entrap another type of molecule (the "guest"). Many different compounds that can form clathrate hydrates have been documented, [1][2][3] but for practical applications the most important the components of natural gas, particularly methane; hence these solids are often termed "gas hydrates", or simply "hydrates". At moderate to high pressures, gas hydrates will form at temperatures that can be significantly above the 273 K. Such conditions are common geologically, in permafrost and at and below the sea floor, and have led to the formation of vast natural deposits of gas hydrates.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17][18][19][20] Recent studies have reported an interesting phenomenon for the inclusion of large guest molecules (LGMs) in the large cages of sII or sH hydrates. [8][9][10][11][12][13][14][15][16][17][18][19][20] It was reported that the trans conformation of some large guest molecules (LGMs), such as n-butane and isopentane, is thermodynamically preferred in the neat phase, but the gauche conformation of LGMs is observed in the large cages of sII or sH hydrates. [8][9][10][11]15 In addition, it was recently reported that some alcohols with molecular sizes above 7.5Å form sII hydrates in the presence of methane gas.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17][18][19][20] It was reported that the trans conformation of some large guest molecules (LGMs), such as n-butane and isopentane, is thermodynamically preferred in the neat phase, but the gauche conformation of LGMs is observed in the large cages of sII or sH hydrates. [8][9][10][11]15 In addition, it was recently reported that some alcohols with molecular sizes above 7.5Å form sII hydrates in the presence of methane gas. 13,19 1-Butanol with a molecular size of 9.05Å and a trans-trans conformation may not be considered as an sII hydrate former from the viewpoint of guest inclusion, but 1-butanol with a molecular size of 7.72Å and a gauche-gauche conformation is reported to be an sII hydrate former in the presence of methane gas.…”
Section: Introductionmentioning
confidence: 99%